Genotoxicidade e equoterapia no controle postural de portadores de esclerose múltipla - Menezes, Karla Mendonça (2011)
Introduction: Multiple Sclerosis (MS) is a chronic neuropathology characterized by infiltration of inflammatory cells in the central nervous system (CNS). Some studies have suggested that cumulative damage to DNA, induced accumulation of reactive oxygen species (ROS) may contribute to several mechanisms underlying the lesions of MS. As a result of dysfunctions observed in different CNS structures, changes in postural control are frequent observations in MS patients. Studies have shown that therapeutic interventions such as equine therapy has the potential to reduce many of the deficiencies observed in MS. Objectives: 1) assess the levels of DNA damage in MS patients, 2) investigate the relationship between rates of DNA damage and parameters of postural control in people with MS, and 3) Verify that hippotherapy is able to initiate changes postural control of patients with MS. Method: The study included 14 MS patients with a mean age of 40.7 ± 8.3 years and 28 healthy controls aged 35.10 ± 15.3 years. The DNA damage was evaluated using the alkaline version of the comet assay. The postural control was assessed by stabilometry for 30 seconds in quiet stance. Results: Patients with MS had higher rates of DNA damage (21.3 ± 4.8) than healthy controls (7.9 ± 6.1) with p = 0.0001. We found no association between rates of DNA damage and the parameters of postural control. After stimulation of hippotherapy, subjects with MS were able to reduce body oscillations Conclusion: MS patients showed more DNA damage than healthy controls. Hippotherapy can be recommended for rehabilitation of postural control in subjects with MS.